Has the prevalence of stunting in South African children changed in 40 years? A systematic review - Said-Mohamed, Rihlat (BMC Public Health, 2015)
BACKGROUND: In the last 20 years, South Africa has experienced political, economic, and demographic transitions accompanied by an epidemiological transition. Like several sub-Saharan countries, the South African population is facing both under–and over–nutrition, and nutrition and lifestyle related chronic disease while the burden of infectious disease remains high. It is critical to understand these trends overtime in order to highlights the pitfalls and successful measures initiatives taken in the efforts to tackle malnutrition. The objective of this systematic review is to investigate the changes in the prevalence of stunting, a chronic form of undernutrition, in South Africa over 40 years, and to derive lessons from the South African experience, a country in an advanced process of transition in sub-Saharan Africa. METHODS: We undertook a systematic review of publications selected from PubMed, Science Direct and Scopus. We included studies and surveys published between 1970 and 2013 if they reported the prevalence of stunting (low height-for-age) in children under-6 years of age living in South Africa. We excluded studies conducted in health facility outpatients or hospital wards, or children with known chronic and acute infectious diseases. We extracted Date of data collection, study setting, ethnicity, age, sex, sample size, growth references/standards, diagnostic criteria for stunting and prevalence of stunting from each study. RESULTS: Over the last decade, the national prevalence of stunting has decreased. However, between and within provincial, age and ethnic group disparities remain. Unlike other countries in sub-Saharan Africa, no sex or rural/urban differences were found in preschool children. However, the analysis of long-term trends and identification of vulnerable groups is complicated by the use of different growth references/standards and sampling methods. CONCLUSION: Despite economic growth, political and social transitions, and national nutritional programs, stunting remains stubbornly persistent and prevalent in South Africa. A multi-sectoral and public health approach is needed to: (i) better monitor stunting over time, (ii) combat malnutrition during the first thousand days of life through continued efforts to improve maternal nutrition during pregnancy and infant feeding practices. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12889-015-1844-9) contains supplementary material, which is available to authorized users.